T-cell response following COVID booster vaccination in seronegative people with multiple sclerosis. Issue 9 (12th August 2022) - Tallantyre, Emma; Vickaryous, Nicola; Richards, Aidan; Rios, Francesca; George, Katila; Scurr, Martin; Godkin, Andrew; Loveless, Samantha; Dobson, Ruth; ,; ,
Abstract : Background: Attenuated vaccine response is a concern in people receiving immunosuppression. It is unclear whether booster vaccinations improve immunity in this context. Methods: T-cell and antibody responses to Sars-COV-2 RBD (spike protein) were measured following third COVID-19 vaccine (v3) in people with MS who were IgG seronegative after vaccines 1&2. Results: 41 people with MS (30:11 female:male; mean age 45.6 years) were included; 28 receiving ocreli- zumab and 6 fingolimod, the remainder were on other immunosuppressants. Samples were taken 4-8 weeks following v3. Anti-RBD seroconversion after v3 occurred in 10/28 (36%) on ocrelizumab and 5/6 (83%) on fingolimod. T-cell responses were detected in 24/28 (86%) treated with ocrelizumab and 0/6 (0%) treated with fingolimod. All those with T-cell responses had seroconverted. There was an association between evidence of previous infection and seroconversion (p=0.0025), but not T-cell response to vaccination following v3 (Fisher's exact p=0.2). Four patients (all on ocrelizumab) had experienced confirmed COVID since March 2020; 2 were admitted to hospital. Conclusions: Seroconversion occurs in a proportion of seronegative people following COVID-19 vaccine dose 3. T-cell response is frequently seen despite the lack of humoral immunity. The clinical correlates of antibody and T cell responses to COVID-19 remain to be established.